Music in the age of the renaissance - Perkins, Leeman L. (New York W. W. Norton & Company, 1999)
A richly detailed portrait of the music and surrounding culture in one of history's most creative eras.Music in the Age of the Renaissance, written by one of the country's leading scholars, brings to life the musical styles and genres that mark this humanistic period of artistic and scientific revolution. In his compelling treatment of how the music was developed and transmitted, Professor Leeman Perkins grounds his narrative firmly in political, religious, social, and cultural history, opening a window onto the lavish courts, magnificent churches, and thriving urban centers in which music played such a vital role. The latest, best, and most comprehensive survey of Renaissance music to appear in over forty years.